Ambient Air Quality and the Incidence of Selected Diseases: Some Urban Health Observations in Lagos, Nigeria (Impact: Journal of Transformation, 2018)
The quality of air is determined by the extent of atmospheric pollution. The USEPA identifiessix criteria pollutants namely particulate matter (PM), ground level ozone, carbonmonoxide, sulphur oxides, nitrogen oxides and lead exposure as toxic and injurious to humanhealth. Thus, there is a need to examine ambient air quality and incidence of selecteddiseases in Lagos, Nigeria. The data for the study include a five-year sampling on criteriapollutants and data on selected airborne diseases that were collected for the same period oftime. Data analysis adopted the use of multiple regression for examining the relationshipbetween ambient criteria pollutants and the occurrence of diseases. GIS procedure was alsoemployed to produce a map showing the spatial pattern of criteria pollutants. The findingsreveal an R2 of 19.8, 13.9, 8.9, 8.4 and 16.8 percent respectively for asthma, bronchitis, heartfailure, lung cancer and tuberculosis. The results show a low level of association and thiswas attributed to other causal factors responsible for the occurrence of the selected diseases.However, this study provides evidence of an association between outdoor air pollution andincreased risk from these diseases. Therefore, the study recommends that governments, andother stakeholders in health sectors should harmonize efforts, resources and ideas towardseffective planning, monitoring, policy implementation and provision of facilities that couldcontrol and ameliorate the presence of pollutants to which urban residents are exposedthereby reducing the health effects from such exposures.